The Nociceptive and Inflammatory Responses Induced by the Ehrlich Solid Tumor Are Changed in Mice Healed of Plasmodium berghei Strain ANKA Infection after Chloroquine Treatment - Maria de Fatima Rodrigues Aguiar; Meiriane Mendes Guterres; Eduarda Magalhães Benarrosh; Waldiceu Aparecido Verri; Cássia Calixto-Campos; Quintino Moura Dias (Journal of Parasitology Research)
Comorbidities that involve infectious and noninfectious diseases, such as malaria and cancer, have been described. Cancer and malaria induce changes in the nociceptive and inflammatory responses through similar pathophysiological mechanisms. However, it is unclear whether malaria and antimalarial treatment can change the inflammatory and nociceptive responses induced by solid cancer. Therefore, the present study experimentally evaluated the effect of infection by Plasmodium berghei strain ANKA and chloroquine treatment on the nociceptive and inflammatory responses induced by the solid Ehrlich tumor in male BALB/c mice. On the 1st experimental day, mice were infected with Plasmodium berghei and injected with tumor cells in the left hind paw. From the 7th to the 9th experimental day, mice were treated daily with chloroquine. The parasitemia was evaluated on the 7th and 10th days after infection. On the 11th experimental day, mice were evaluated on the von Frey filament test, the hot plate test, and the paw volume test. At the end of the experimental tests on the 11th day, the peripheral blood of all mice was collected for dosing of IL-1β and TNF-α. The blood parasitemia significantly increased from the 7th to the 10th day. The chloroquine treatment significantly decreased the parasitemia on the 10th day. The presence of the tumor did not significantly change the parasitemia on the 7th and 10th days in mice treated and nontreated with chloroquine. On the 11th day, the mechanical and thermal nociceptive responses significantly increased in mice with tumors. The treatment with antimalarial significantly reduced the mechanical nociceptive response induced by tumors. The hyperalgesia induced by tumors did not change with malaria. The mechanical and thermal hyperalgesia induced by the tumor was significantly reduced in mice treated and healed from malaria. On the 11th day, the volume of the paw injected by the tumor was significantly increased. The mice treated with chloroquine, infected with malaria, or healed of malaria showed reduced paw edema induced by the tumor. Mice with tumors did not show a change in IL-β and TNF-α serum levels. Mice with tumors showed a significant increase in serum levels of IL-1β but not TNF-α when treated with chloroquine, infected with malaria, or healed of malaria. In conclusion, the results show that malaria infection and chloroquine treatment can influence, in synergic form, the nociceptive and inflammatory responses induced by the solid tumor. Moreover, the mechanical antinociception, the thermal hyperalgesia, and the antiedema effect observed in mice treated with chloroquine and healed from malaria can be related to the increase in the serum level of IL-1β.